2010
DOI: 10.1101/lm.1504010
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin-proteasome pathway and synaptic plasticity

Abstract: Proteolysis by the ubiquitin-proteasome pathway (UPP) has emerged as a new molecular mechanism that controls wideranging functions in the nervous system, including fine-tuning of synaptic connections during development and synaptic plasticity in the adult organism. In the UPP, attachment of a small protein, ubiquitin, tags the substrates for degradation by a multisubunit complex called the proteasome. Linkage of ubiquitin to protein substrates is highly specific and occurs through a series of well-orchestrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 140 publications
1
123
1
Order By: Relevance
“…Moreover, our biochemical data show that UPS-dependent degradation is controlled by the activity status and contributes to remodeling of synaptic protein complexes in a highly substrate-specific manner. The target specificity of UPSdependent degradation is ascribed to the high selectivity of ubiquitin-ligating enzyme complexes for their targets (Hegde, 2010). Therefore, we suggest that the regulated ubiquitin conjugation to presynaptic scaffolds might control their differential activity status-dependent degradation by UPS observed in our experiments.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, our biochemical data show that UPS-dependent degradation is controlled by the activity status and contributes to remodeling of synaptic protein complexes in a highly substrate-specific manner. The target specificity of UPSdependent degradation is ascribed to the high selectivity of ubiquitin-ligating enzyme complexes for their targets (Hegde, 2010). Therefore, we suggest that the regulated ubiquitin conjugation to presynaptic scaffolds might control their differential activity status-dependent degradation by UPS observed in our experiments.…”
Section: Discussionmentioning
confidence: 71%
“…result of alteration in protein synthesis and/or protein degradation. Formation of long-term memory is dependent on both phenomena (38). The major changes in de novo protein synthesis appear hours after induction of long-term plasticity (15,35).…”
Section: Resultsmentioning
confidence: 99%
“…Studies over the last decade demonstrate strong links between maintenance of long-term potentiation (LTP, a type of long-term synaptic plasticity) and protein degradation ((37); for review, see (38)). It was recently shown that inhibition of the proteasome system may enhance LTP induction (39) because of prevention of translation activator targeting (40).…”
mentioning
confidence: 99%
“…We observed that UCH-L1 is a target of oxidative damage in DS and DS/AD brains, and its oxidative modification likely leads to a decreased function as demonstrated by activity assay [80,81]. One of the major consequences of aberrant UCH-L1 activity is an impaired proteasome proteolytic system, which will lead to accumulation of damaged proteins and formation of protein aggregates [20,97,[115][116][117]. To confirm this hypothesis we measured the trypsin-like, chymotrypsin-like, and caspaselike activities of the proteasome demonstrating decreased levels that suggest a reduced activity of UPS in DS brain [81].…”
Section: Oxidative Damage To Proteostasis Network In Dsmentioning
confidence: 99%